Novel Variants of CEP152 in a Case of Compound-Heterozygous Inheritance of Epilepsy - Li, Weiran; Lu, Xiaowei; Shu, Jianbo; Cai, Yingzi; Li, Dong; Cai, Chunquan (Global Medical Genetics, 2024)
Introduction CEP152 encodes protein Cep152, which associates with centrosome function. The lack of Cep152 can cause centrosome duplication to fail. CEP152 mutates, causing several diseases such as Seckel syndrome-5 and primary microencephaly-9.Methods In this study, we reported a patient diagnosed with epilepsy in Tianjin Children's Hospital. We performed clinical examination and laboratory test, and whole-exome sequencing was performed for the proband's and his parents' peripheral blood. The suspected compound-heterozygous variant in the CEP152 gene was verified by Sanger sequencing and quantitative real-time polymerase chain reaction technology.Results We discovered three variants—two of them from CEP152 and one from HPD. The result showed the variants in CEP152 only. The patient presented with seizures frequently. Sanger sequencing showed two novel variants in CEP152 are in exon26 (NM_014985.3 c.3968C > A p.Ser1323*) and in exon16 (NM_014985.3 c.2034_2036del p.Tyr678*).Conclusions We reported a novel compound-heterozygous variant in the CEP152 gene in this study. Most of the phenotypes are Seckel syndrome and primary microencephaly, and the novel variant may cause an atypical phenotype that is epilepsy.
Keywords: CEP152; compound-heterozygous; variants; phenotypes; WES; Sanger sequencing